2016
DOI: 10.1681/asn.2014101044
|View full text |Cite
|
Sign up to set email alerts
|

Somatic Mutations Modulate Autoantibodies against Galactose-Deficient IgA1 in IgA Nephropathy

Abstract: Autoantibodies against galactose-deficient IgA1 drive formation of pathogenic immune complexes in IgA nephropathy. IgG autoantibodies against galactose-deficient IgA1 in patients with IgA nephropathy have a specific amino-acid sequence, YCS, in the complementarity-determining region 3 of the heavy chain variable region compared with a YCA sequence in similar isotype-matched IgG from healthy controls. We previously found that the S residue is critical for binding galactose-deficient IgA1. To determine whether t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 31 publications
(18 citation statements)
references
References 30 publications
0
17
1
Order By: Relevance
“…These autoantibodies share an unusual sequence in the complementarity-determining region 3 of the variable region of their heavy chains that enhances binding to galactose-deficient glycans,[ 8 ] apparently as a result of a somatic mutation. [ 28 ] The clinical observation that many IgAN patients have renal biopsies without mesangial IgG by standard immunofluorescence staining may seem at odds with our current findings. However, glomerular IgG can be found frequently in these biopsy specimens when using high-resolution confocal microscopy imaging coupled with immunofluorescence staining.…”
Section: Discussioncontrasting
confidence: 54%
“…These autoantibodies share an unusual sequence in the complementarity-determining region 3 of the variable region of their heavy chains that enhances binding to galactose-deficient glycans,[ 8 ] apparently as a result of a somatic mutation. [ 28 ] The clinical observation that many IgAN patients have renal biopsies without mesangial IgG by standard immunofluorescence staining may seem at odds with our current findings. However, glomerular IgG can be found frequently in these biopsy specimens when using high-resolution confocal microscopy imaging coupled with immunofluorescence staining.…”
Section: Discussioncontrasting
confidence: 54%
“…For example, these antibodies are susceptible to bacteria-derived proteases (13). Recent data suggest that anti-glycan autoantibodies may be targeting IgA VH gene segments that occur as a result of somatic hypermutation, and not sequences present in the host germline (14).…”
Section: Disease Pathogenesis In Iganmentioning
confidence: 99%
“…Conversely, introducing Ser residue in the third position of CDR3 of the heavy chains of IgG from a healthy control increased the binding of the IgG to Gd-IgA1 ( 182 ). Recent study has shown that Ser in CDR3 in the heavy chains of IgG autoantibodies originates from somatic mutations rather than from rare variants of VH genes ( 183 ).…”
Section: Autoantibodies Against Galactose-deficient Iga1 In Iga Nephrmentioning
confidence: 99%